3D flow and heat transfer of micropolar fluid suspended with mixture of nanoparticles (Ag-CuO/H2O) driven by an exponentially stretching surface. Issue 6 (9th May 2020) - Manjunatha, S.; Ammani Kuttan, B.; Ramesh, G.K.; Gireesha, B.J.; Aly, Emad H.
Abstract : Purpose: The purpose of this paper is to discuss the 3D micropolar hybrid (Ag-CuO/H2 O) nanofluid past rapid moving surface, where porous medium has been considered. Design/methodology/approach: The model of problem was represented by highly partial differential equations which were deduced by using suitable approximations (boundary layer). Then, the governing model was converted into five combined ordinary differential equations applying proper similarity transformations. Therefore, the eminent iterative Runge–Kutta–Fehlberg method (RKF45) has been applied to solve the resulting equations. Findings: Higher values of vortex viscosity, spin gradient viscosity and micro-inertia density parameters are reduced in horizontal direction, whereas opposite behaviour is noticed for vertical direction. Originality/value: The work has not been done in the area of hybrid micropolar nanofluid. Hence, this article culminates to probe how to improve the thermal conduction and fluid flow in 3D boundary layer flow of micropolar mixture of nanoparticles driven by rapidly moving plate with convective boundary condition.